Extraction of noble metal ions from aqueous solution by ionic liquids - Lee, Jong-Min (2013)
Nine ionic liquids containing pyridinium, pyrrolidinium and piperidinium cations with anion bis(trifluoromethylsulfonyl)imide were synthesized to investigate the ability of ionic liquids to extract silver, palladium, or gold metal ions from water at room temperature. Results are reported for distribution coefficients and extraction percentages with these ionic liquids. Ionic liquids containing a disulfide group or a nitrile group exhibit good extraction properties for silver or palladium ions. Gold ions were efficiently and selectively extracted with these functionalized ionic liquids. The influence of the mass ratio of water to ionic liquid on distribution coefficient or extraction percentage for aqueous gold ions was evaluated.